ANTIINFLAMMATORY EFFECTS OF Cinnamyl tiglate CONTAIN IN VOLATILE OIL OF KUNYIT (Curcuma domestica Val.) - Oktavia Salasia, Sri Isrina; ., Rochmadiyanto; Fatimah, Oktarina (Indonesian Journal of Pharmacy, 2002)
The aim of this study was to evaluate the antiinflammatory effects of the cinnamyl tiglate contain in the volatile oil of kunyit (Curcuma domestica Val.) on the carrageenin induced inflammatory in Wistar albino rats (Rattus norvegicus). Cinnamyl tiglate was isolated using thin layer chromatography with the silica gel GF as stationary phase and the hexane with toluene as a mobile phase. Cinnamyl tiglate could be isolated using gas chromatography and mass spectrometry (GCMS). Inflammation of rats were induced by 1% carrageenin subplantar followed with oral administration of the cinnamyl tiglate at various doses of 1,1%, 4,4%, and 17,6%/kg bw. As controle were used rats treated orally with aspirin 450 mg/kg bw and volatile oil of kunyit 1,2 ml/kg bw. The volume of inflammations were measured with pletismograph. The analysis of GCMS showed that cinnamyl tiglate could be isolated from volatyle oil of kunyit in the second fraction with the concentration of 63,62%. Cinnamyl tiglate with dose of 1,1%/kg bw had no effects on the inflammatory reactions (P≥0,05). Cinnamyl tiglate with dose of 4,4%/kg bw could decrease the inflammatory reactions (P≤0,05) and with dose of 17,6%/kg bw the antiinflammatory effects were more significant (P≤0,01).Key words: Cinnamyl tiglate, Curcuma domestica Val., antiinflammatory